FAKTOR-FAKTOR DETERMINAN PENGETAHUAN DAN PERSEPSI MASYARAKAT TENTANG BANGUNAN BERLANGGAM BALI - Ngakan Putu Sueca; Ida Bagus Gede Primayatna; Ketut Muliawan S.; Wayan Nada; Dw. Nym. Wastika (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2001)
The objective of this study is to know determinant factors of people knowledge about Balinese tradisional architecture and to know determinant factors of Balinese perception on Balinese style buildings and to explain factors that affect them. The research uses cross-sectional sample survey. Data are collected by interview techniques with questionnaire as the main instuments. Sampling techniques which is used is stratified random sampling. Data is analyzed descriptively and analytically (using variance analysis). Among eigth variables which planned to be axamined, only six variables can be analyzed statistically (respondent status, sex, education, working experience on building construction, ability in reading Balinese character, and intensity in reading